2022
DOI: 10.1111/evo.14546
|View full text |Cite
|
Sign up to set email alerts
|

Genomic resolution of cryptic species diversity in chipmunks

Abstract: Discovery of cryptic species is essential to understand the process of speciation and assessing the impacts of anthropogenic stressors. Here, we used genomic data to test for cryptic species diversity within an ecologically well‐known radiation of North American rodents, western chipmunks (Tamias). We assembled a de novo reference genome for a single species (Tamias minimus) combined with new and published targeted sequence‐capture data for 21,551 autosomal and 493 X‐linked loci sampled from 121 individuals sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 107 publications
(220 reference statements)
0
2
0
Order By: Relevance
“…An evaluation of nearly 600 bp of COI revealed that approximately 75% of Anastrepha species can successfully be identified using this approach, but it does not discriminate members of the A. fraterculus cryptic complex and some other closely related species of the fraterculus group (Barr et al, 2018 ; Bartolini et al, 2020 ). On the other hand, genomic data coupled with multispecies coalescent approaches have provided invaluable information on evolutionary histories of cryptic species complexes in a great variety of animal taxa, such as insects, mammals, reptiles, and birds (Dupuis, Bremer, et al, 2018 ; Herrera et al, 2022 ; Obiol et al, 2023 ; Singhal et al, 2018 ; Thawornwattana et al, 2018 ; Zhang et al, 2021 ), as well as plants, such as ferns and angiosperms (Kinosian et al, 2020 ; Wu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…An evaluation of nearly 600 bp of COI revealed that approximately 75% of Anastrepha species can successfully be identified using this approach, but it does not discriminate members of the A. fraterculus cryptic complex and some other closely related species of the fraterculus group (Barr et al, 2018 ; Bartolini et al, 2020 ). On the other hand, genomic data coupled with multispecies coalescent approaches have provided invaluable information on evolutionary histories of cryptic species complexes in a great variety of animal taxa, such as insects, mammals, reptiles, and birds (Dupuis, Bremer, et al, 2018 ; Herrera et al, 2022 ; Obiol et al, 2023 ; Singhal et al, 2018 ; Thawornwattana et al, 2018 ; Zhang et al, 2021 ), as well as plants, such as ferns and angiosperms (Kinosian et al, 2020 ; Wu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tamias senex was long treated as a subspecies of T. townsendii , but the latter taxon is now recognized as four distinct species (Gannon and Forbes 1995). The sister taxon to the rest of the townsendii species group is the Long-eared Chipmunk ( T. quadrimaculatus ; Reid et al 2012; Herrera et al 2022). Restricted to the Sierra Nevada, the geographic range of T. quadrimaculatus is almost completely overlapped by that of T. senex (ca.…”
Section: Methodsmentioning
confidence: 99%